KETIKA PENAMPILAN MENJADI TOLOK UKUR: WELAS DIRI DAN KECEMASAN PENAMPILAN SOSIAL PADA MAHASISWA PENGGUNA INSTAGRAM - Tumanggor, Raja Oloan; Okta Febri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasingly intense use of social media, particularly the visual-based Instagram, has led to students being more frequently exposed to ideal appearance standards. This condition can trigger social appearance anxiety, which is anxiety related to how a person perceives their physical appearance in front of others. This study aims to determine the role of self-compassion in reducing levels of social appearance anxiety in college students who use Instagram in Jakarta. Self-compassion is understood as a person's ability to be warm, accepting, and non-judgmental when faced with imperfections or social pressure. The study used a quantitative approach with a survey method of college students who use Instagram in Jakarta. The instruments used included the Self-compassion and Social Appearance Anxiety scales that have been adapted into Indonesian. Data analysis was conducted using correlation and regression tests to determine the extent to which self compassion contributes to levels of social appearance anxiety. The results showed that self compassion plays a significant role in reducing social appearance anxiety. Students with higher levels of self compassion tend to have lower levels of appearance anxiety, suggesting that self-compassion may be a protective factor against social pressures arising from Instagram use. The results of the Spearman correlation analysis showed a significant negative relationship between social anxiety and self-fear (ρ = −0.401; p < 0.001). This indicates that social appearance anxiety in students who use Instagram in Jakarta is negatively correlated with their level of self-compassion. This finding emphasizes the importance of developing self-compassion as a mental health strategy for students in the social media era. This study also opens up opportunities for the development of intervention programs such as mindfulness training, self-acceptance, or digital literacy aimed at helping students use Instagram more healthily and reduce appearance-related anxiety.